Who is almighty?. Issue 2 (June 2021) - KODAJ, DANIEL
Abstract: Peter Geach recommended conceiving of God as almighty, not as omnipotent. I argue that Geach's heuristic explanation of almightiness does not provide a workable definition, and I propose one on his behalf. The resulting notion turns out to have precisely those theoretical virtues that Geach advertised: it is immune to the logical puzzles that bedevil omnipotence, and it is better suited to religious contexts than the notion of maximal power that informs typical definitions of omnipotence.